ANALISIS PELAKSANAAN LAYANAN RAKYAT UNTUK SERTIFIKAT TANAH (LARASITA) DI KANTOR PERTANAHAN KOTA SAMARINDA - Mohammad Eddy Saputra (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
The objective of this research is to know how National Land Agency Policy Implementation Number 18 Year 2009 About People Service for Land Certificate (Larasita) at Land Office in Samarinda city. The results showed that in the process of Larasita Program implementation problems encountered in the implementation of Larasita program in Samarinda city that is not optimally the policies and programs of various sectors that affect the life of the people such as human resources, the equipment resource factors are still limited ie the Internet network that has not reached The areas visited by Larasita cars, the factors of communication and information provided by the Larasita team are less effective so there are still many people who are confused about the requirements to complete the documents in the land certificate management.